Comportamento mecânico da liga Ti-6Al-4V com superfície modificada por laser de femtosegundo para uso biomédico - Santos, Alan dos (2012)
Stainless steel orthopedic implants are still the most widely used in Brazil due to their lower cost. There is, however, a tendency to expand the use of special alloys such as titanium-based, due to clinical advantages that they present, notably the low modulus of elasticity and the best biocompatibility among the metallic biomaterials. The surface treatments aim to develop substrates suitable for bone growth, thus preventing the implantation of the prosthesis with PMMA cement, which results in an efficient mechanical fixing, but there is no biological interaction between implant and bone. There are several surface modification techniques, all of them improving at some level the process of osseointegration. However, researches have focused on biological aspects of the process and, despite the durability of the implant, there is currently no objective information in the literature about the influence of surface treatments on the mechanical behavior under cyclic stresses. The laser surface modification emerges as a promising alternative, since it permits precise control of parameters, regular surface development, induces reduced mechanical and thermal damage, and is known to promote osseointegration. The femtosecond laser, in particular, allows pulses of short duration (10-15s), reducing even more the damage caused by heat input. This study evaluated the influence of surface modification by femtosecond LASER in the fatigue resistance of Ti-6Al-4V alloy samples. S-N curves were determined for the reference samples and for the samples with modified surface. The topography developed and the fracture surfaces were analyzed by scanning electron microscopy. The femtosecond LASER has developed a regular surface with a bimodal distribution of microcolumns and ripples, and did not cause severe damage adjacent to the modified surface, however, has significantly reduced fatigue resistance.